THE CORRELATION OF MOTHER'S KNOWLEDGE AND MOTHER'S BEHAVIOR IN STUNTING PREVENTION EFFORTS IN TUNTUNGAN VILLAGE 2 DELI SERDANG REGENCY - Dhani Syahputra; Ida Yustina; Nurmaini Nurmaini; Kintoko Rochadi; Fikarwin Zuska (International Journal of Midwifery Research, 2023)
Stunting is a situation of unbalanced nutrition which is a physical growth disorder and a decrease in the speed of growth in children. Nutritional problems related to stunting is still a problem that occurred in Indonesia. The long-term impact that occurs due to stunting is still physical, mental, intellectual and cognitive development disorders. The incidence of stunting in children with high resulted in the long-term problems and difficult to control so that it will cause a risk to off spring who will be vulnerable to a low birth weight. Nutrition survey data over the past year shows that nutritional problems are still high, one of which is stunting, which is the main problem. The role of the mother in the family greatly affects food preparation so that the mother's knowledge is needed to improve the nutrition of their family members. The purpose of this study was to determine the relationship between mother's knowledge and mother's behavior in preventing stunting in Tuntungan Village 2, Pancur Batu District, Deli Serdang Regency. This study was conducted on  mothers who have toddlers aged 6-59 months and this research is a qualitative research with an phenomenological approach. Mother's knowledge is very important in preventing stunting. Mothers who have good knowledge will be very influential in preventing stunting in the family. The importance of collaboration with all layers in order to support increasing maternal knowledge in preventing stunting.